LACHIO RECREATIONAL PARK'S MARKETING STRATEGY FOR ATTRACTING VISITORS USING SOCIAL MEDIA MARKETING - Melati Melati; Hasan Sazali; Sori Monang (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: Technological sophistication has a significant impact on its users, including entrepreneurs/businessmen. Through the use of technology, small, medium, and large entrepreneurs can promote their efforts to make it easy for consumers to understand. Luchio Recreation Park, for example, is a micro-enterprise that utilizes advanced technology in marketing its tourism. Through the Facebook and Instagram platforms, Luchio Recreation Park tours are able to attract the interest of visitors. For this reason, this study aims to find out how digital marketing through social media attracts visitors. This study used qualitative research methods. Research that focuses on the in-depth process of the interrelationship of phenomena studied by researchers. Determination of the sample in this study was selected using purposive sampling technique. The primary data was obtained directly from key entities or sources relevant to this research, namely from social media account managers and lachio recreation park owners. The secondary data that the researcher obtained was obtained through documentation in the form of promotional posts carried out. The instruments in the study were interview guides, recording equipment, portrait tools, and stationery. There are 3 data collection techniques, namely, observation, interviews, and documentation. The data analysis technique used in this research is the data analysis of the Miles and Huberman model using 3 parts of the analysis that go hand in hand, namely; data reduction, data presentation and conclusion drawing/verification. The results of the study indicate that the strategies used in carrying out promotional activities through social media are in accordance with the 4C theory, namely context, communication, collaboration, and connection. In context, the Lachio theme park account pays attention to the quality of the content, both photos or videos as well captions , in communication, has the principle of always being open and friendly to comments submitted and honest, in collaboration Lachio theme park accounts work together with accounts entertainment and news information provider who has thousands of followers to be able to help promote shared content to expand reach and admin interacts with visitors to tag or mark Lachio recreation park, and on connection, admin @tamanrekreasilachio posts up to date every day. So, by implementing these 4 things, you can streamline the success of the Lachio Recreation Park in an effort to attract visitors through social media. Keywords: Communication Strategy, Social Media, Interests of Visitors